Synthesis, α-glucosidase inhibition, α-amylase inhibition, and molecular docking studies of 3,3-di(indolyl)indolin-2-ones - Santoso, Mardi (2023)
The synthesized 3,3-di(indolyl)indolin-2-ones 1a-p showed desired higher α-glucosidase inhibitory activities and lower α-amylase inhibitory activities than standard drug acarbose. Particularly, compound 1i showed favorable higher α-glucosidase % inhibition of 67 ± 13 and lower α-amylase % inhibition of 51 ± 4 in comparison to acarbose with % inhibition activities of 19 ± 5 and 90 ± 2, respectively. Docking studies of selected 3,3-di(indolyl)indolin-2-ones revealed key interactions with the active sites of both α-glucosidase and α-amylase, further supporting the observed % inhibitory activities. Furthermore, the binding energies are consistent with the % inhibition values. The results suggest that 3,3-di(indolyl)indolin-2-ones may be developed as suitable Alpha Glucosidase Inhibitors (AGIs) and the lower α-amylase activities should be advantageous to reduce the side effects exhibited by commercial AGIs.